2015
DOI: 10.1002/cncr.29364
|View full text |Cite
|
Sign up to set email alerts
|

Detection of K‐ras gene mutation by liquid biopsy in patients with pancreatic cancer

Abstract: BACKGROUND: Cell-free circulating tumor DNA (ctDNA) in serum has been considered to be a useful candidate for noninvasive cancer diagnosis. The current study was designed to estimate the clinical usefulness of genetic analysis for ctDNA by digital polymerase chain reaction in patients with pancreatic cancer. METHODS: The authors compared K-ras mutations detected in endoscopic ultrasound-guided fine-needle aspiration biopsy tissue DNA and in ctDNA from 75 patients with pancreatic cancer. K-ras mutations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
4
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(116 citation statements)
references
References 34 publications
5
104
4
3
Order By: Relevance
“…As KRAS is not yet established as a clinically relevant biomarker in PDAC, future translational trials in pancreatic cancer that evaluate a broad range of novel biomarkers should, at least to our opinion, include a repeated biomarker assessment during the course of disease within their prospective study protocols. Novel promising techniques like liquid biopsy approaches may thereby help to overcome the limitations of obtaining tumor tissue safely in PDAC [25]. As it may be difficult to obtain sufficient tumor tissue in PDAC by percutaneous- or endosonography-guided biopsy techniques, a sampling error may occur specifically in the light of tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…As KRAS is not yet established as a clinically relevant biomarker in PDAC, future translational trials in pancreatic cancer that evaluate a broad range of novel biomarkers should, at least to our opinion, include a repeated biomarker assessment during the course of disease within their prospective study protocols. Novel promising techniques like liquid biopsy approaches may thereby help to overcome the limitations of obtaining tumor tissue safely in PDAC [25]. As it may be difficult to obtain sufficient tumor tissue in PDAC by percutaneous- or endosonography-guided biopsy techniques, a sampling error may occur specifically in the light of tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor receptor is the most common biomarker used to diagnose these rare cancers . However, certain specific receptors such as tyrosine protein kinase Met (MET) and ROS1 have been found as biomarkers for rare types of cancers . In spite of these receptors as biomarkers, specificity remains as a major challenge for targeted cancer treatments.…”
Section: Types Of Cancer and Biomarkersmentioning
confidence: 99%
“…Kinugasa et al demonstrated that the measurements of KRAS mutation in patients with pancreatic cancer appeared to be an early monitoring tool for treatment efficacy [30]. Our initial pilot study in patients with pancreatic cancer demonstrated cf DNA could detect responses reliably prior to changes seen on conventional imaging [40].…”
Section: Novel Serum Biomarkersmentioning
confidence: 99%